An Introduction to the Special Feature on the Biden Nuclear Posture Review. Issue 2 (3rd July 2021) - Abe, Nobuyasu
ABSTRACT: The US Biden administration is conducting its Nuclear Posture Review (NPR); the resulting report is expected to come out in early 2022. In this introductory essay to the special feature on the upcoming NPR and its implications for US Asian allies, the guest editor Nobuyasu Abe provides an overview of three articles.